The Global Urban Monitoring Approach Taken by UN-Habitat. Recent Experiences on Implementing SDG 11, - Mwaniki, Dennis; Ndugwa, Robert (Steiner, 2021)
UN-Habitat bases its worldwide urban development monitoring system on National Samples of Cities and the Global Human settlement Layer. Monitoring the development of built-up areas for settlement and transport purposes under the Sustainable Development Goal 11.3.1 constitutes one of the basic elements of UN-Habitat's Data and Analytic Section.
Keywords: Nachhaltige Stadtentwicklung; Monitoring; Raumbeobachtung; Berichterstattung; Urbanisierung; Internationaler Vergleich; Internationale Organisation; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung